PERILAKU DINAMIS STRUKTUR BETON BERTULANG DARI GEDUNG BERATURAN DENGAN DAKTILITAS (Nilai R) SUBSISTEM STRUKTUR YANG BERBEDA - Sudarsana, I K.; Sugupta, D.P.G; Udara, I G.N.K. (Jurnal Ilmiah Teknik Sipil, 2012)
In the SNI 03-1726-2002 Standard Clause 4.3.5 it is stated that “When a structural system parallel to the direction of nominal earthquake load, consists of some sub-structural systems, the representative reduction factor (Rr) of the earthquake load for this structure in the direction of the earthquake load can be calculated as an average of weighting values with each sub-structural system base shear as its weighting factors”. With the representative reduction factor (Rr), the base shear acting on the structure does not consider the weakest sub-system which reaches its yielding capacity first, whereas base on stiffness concept, sub-system with a different ductility will resist a different base shear. In order to investigate dynamic behavior of a structure due to this both earthquake loading condition, analysis was done on a reinforced concrete structure of a regular building consisted of structural sub-systems of shear walls and frames which have each different ductility. This both loading conditions are the earthquake with reduction factor of Rr and Rs. Dynamic behavior of the structure is obtained from the results of modeling and analysis of the structure using finite element software (SAP 2000). The calculation was done in two stages in which the first stage, the structure was designed to resist both gravity load and earthquake load. In the design process, earthquake load was treated as static equivalent earthquake load with a reduction factor calculated according to SNI 03-1726-2002 requirements. The second stage, the structure that has been designed, its dynamic behavior was evaluated using nonlinear static pushover analysis including period, base shear, horizontal drift, stiffness, damping and other dynamic properties of the structures. The results of analysis show that dynamic behaviors of the structure subjected to earthquake load with representative reduction factor (Rr) differ from those of the earthquake load with reduction factor each sub-system (Rs). For earthquake load with reduction factor Rs, the actual ductility factor, actual earthquake reduction factor, effective period of the structure are bigger than those of the structure with reduction factor Rr. However, it has smaller base shear, less number of plastic hinges and smaller effective damping.
Keywords: Dynamic behavior, pushover analysis, ductility, reinforced concrete structure